Association of Refractory Pain in the Acute Phase After Subarachnoid Hemorrhage With Continued Outpatient Opioid Use. (11th May 2021) - Jaffa, Matthew N.; Podell, Jamie E.; Smith, Madeleine C.; Foroutan, Arshom; Kardon, Adam; Chang, Wan-Tsu W.; Motta, Melissa; Parikh, Gunjan Y.; Sheth, Kevin N.; Badjatia, Neeraj; Armahizer, Michael J.; Simard, J. Marc; et al.
Abstract : Objective: Little is known about the prevalence of continued opioid use following aneurysmal subarachnoid hemorrhage (aSAH) despite guidelines recommending their use during the acute phase of disease. We sought to determine prevalence of opioid use following aSAH and test the hypothesis that acute pain and higher inpatient opioid dose increased outpatient opioid use. Methods: We reviewed consecutively admitted patients with aSAH from November 2015 through September 2019. We retrospectively collected pain scores and daily doses of analgesics. Pain burden was calculated as area under the pain-time curve. Univariate and multivariable regression models determined risk factors for continued opioid use at discharge and outpatient follow-up. Results: We identified 234 patients with aSAH with outpatient follow-up. Continued opioid use was common at discharge (55% of patients) and follow-up (47% of patients, median 63 [interquartile range 49–96] days from admission). Pain burden, craniotomy, and racial or ethnic minority status were associated with discharge opioid prescription in multivariable analysis. At outpatient follow-up, pain burden (odds ratio [OR] 1.88, 95% confidence interval [CI] 1.5–2.4), depression (OR 3.1, 95% CI 1.1–8.8), and racial or ethnic minority status (OR 2.1, 95% CI 1.1–4.0) were independently associated with continued opioid use; inpatient opioid dose was not. Conclusion: Continued opioid use following aSAH is prevalent and related to refractory pain during acute illness, but not inpatient opioid dose. More efficacious analgesic strategies are needed to reduce continued opioid use in patients following aSAH. Classification of Evidence: This study provides Class II evidence that continued opioid use following aSAH is associated with refractory pain during acute illness but not hospital opioid exposure.